2010
DOI: 10.1152/ajpgi.00178.2009
|View full text |Cite
|
Sign up to set email alerts
|

AE2 Cl/HCO3exchanger is required for normal cAMP-stimulated anion secretion in murine proximal colon

Abstract: Gawenis LR, Bradford EM, Alper SL, Prasad V, Shull GE. AE2 Cl Ϫ /HCO 3 Ϫ exchanger is required for normal cAMP-stimulated anion secretion in murine proximal colon. Am J Physiol Gastrointest Liver Physiol 298: G493-G503, 2010. First published January 28, 2010 doi:10.1152/ajpgi.00178.2009.-Anion secretion by colonic epithelium is dependent on apical CFTR-mediated anion conductance and basolateral ion transport. In many tissues, the NKCC1 NaϪ cotransporter mediates basolateral Cl Ϫ uptake. However, additional ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…AE2 is expressed at high levels in parietal cells of the gastric epithelium, and null mice display a dramatic gastric epithelial phenotype with abnormal canaliculae and reduced HCl secretion (Gawenis et al 2004). Other Cl-secreting epithelia are also affected, notably the proximal colon (Gawenis et al 2010); the role of AE2 has been difficult to establish in most tissues because it is electrically silent, there are no specific inhibitors available, and AE2-null mice die soon after birth. AE2 is expressed in the basolateral membrane of Calu-3 cells (Loffing et al 2000), and recent studies of a stable, AE2-deficient Calu-3 cell line under open-circuit conditions revealed that AE2 mediates most basolateral anion exchange ) and accounts for up to 70% of the net Cl 2 flux during cAMPstimulated fluid secretion .…”
Section: Basolateral Anion Exchange (Ae)mentioning
confidence: 99%
“…AE2 is expressed at high levels in parietal cells of the gastric epithelium, and null mice display a dramatic gastric epithelial phenotype with abnormal canaliculae and reduced HCl secretion (Gawenis et al 2004). Other Cl-secreting epithelia are also affected, notably the proximal colon (Gawenis et al 2010); the role of AE2 has been difficult to establish in most tissues because it is electrically silent, there are no specific inhibitors available, and AE2-null mice die soon after birth. AE2 is expressed in the basolateral membrane of Calu-3 cells (Loffing et al 2000), and recent studies of a stable, AE2-deficient Calu-3 cell line under open-circuit conditions revealed that AE2 mediates most basolateral anion exchange ) and accounts for up to 70% of the net Cl 2 flux during cAMPstimulated fluid secretion .…”
Section: Basolateral Anion Exchange (Ae)mentioning
confidence: 99%
“…Functional studies in genetically engineered animal models that examined the Cl Ϫ /HCO 3 Ϫ anion exchanger 2 (AE2), the SLC26A6 and SLC26A3 Cl Ϫ /HCO 3 Ϫ exchangers, and the sodium/bicarbonate (Na ϩ /HCO 3 Ϫ ) cotransporter (NBC) family members revealed critical roles for bicarbonate secretion in specific intestinal segments along the proximal-distal axis of the intestine (3,10,11,36,76). In addition to its established central role in chloride secretion, the cystic fibrosis transmembrane conductance regulator (CFTR) is now recognized as a critical regulator of intestinal bicarbonate secretion (25,44,67,77).…”
mentioning
confidence: 99%
“…This had no effect on the forskolin-stimulated ⌬I sc (⌬I sc forskolin control29±13Acm -2 and following incubation with acetazolamide ⌬I sc forskolin23±7Acm -2 , N4). Similarly, pre-treatment with acetazolamide and serosal DIDS (1mmoll -1 ), to prevent compensatory up regulation of alternative transporters (Gawenis et al, 2010), had no effect on the forskolin-stimulated I sc and nor did the NHE inhibitor EIPA (100moll -1 serosal, data not shown), demonstrating that the secretion of HCO 3 -produced by hydration of CO 2 does not contribute to the forskolin-stimulated ⌬I sc .…”
Section: +mentioning
confidence: 87%